Dietary zinc and malignant processes (Revista Española de Fisiología, 1974)
Dietary Zinc and Malignant Processes. Rev. esp. Fistol., 30, 97-102. 1974.It study if there is any difference in the plasmatic zinc concentration, determined by atomic absorption spectrophotometry, or in its turnover, determined by the use of ZnGB, in healthy birds and in the ones affected by a malignant tumor. It also study the influence that different treatments of dietary zinc have on that valúes.It have found that the zinc concentration doesn’t increase but the plasm zinc turnover docs speed as a response to a bigger necessity of zinc by the tissues of the patterns affected by a malignant tumor. The turnover also increases and the clasic lymphocytic proliferation of the affected patterns is also found in non affected patterns fed with a big overloaded dietary zinc.